Exploring Senior Management Support in the Implementation of the Results Based Management System in Zimbabwe’s Schools Sector - Jaricha, Ruth; Dzimiri, Wonderful; Jaricha, Ruth (Advances in Social Sciences Research Journal, 2019)
This article made an analysis of the involvement of senior management in the implementation of the Results Based Management System in schools. This was amid concerns from educators that they were finding it difficult to effectively and meaningfully implement the RBM System in schools. The interpretivist/constructivist research paradigm underpinned our study, hence a qualitative research approach was employed. This was a case study of two schools. The population for the study was sixty-eight (68) schools both primary and secondary with a teacher population of nine hundred and forty-nine (949) teachers. Two schools (one primary and the other secondary) were purposefully selected to participate in the study. Thus, twenty-nine (29) teachers and the two (2) school heads became the sample for the study. Included in the sample were the District Schools Inspector and the Education Inspector in the district. Data were generated through in-depth interviews, focus group discussions, observation and document analysis. As such these instruments enhanced the triangulation of the data generated. Data analysis was done concurrently with data generation. Major findings were that senior management in education, starting with the school head through to Head Office personnel, were not visible in schools and the district to assess whether the RBM System was meeting its intended objectives. Of further concern to educators was senior management’s failure to address issues of educators’ training, availability of resources, incentives and feedback which indeed were the province of senior managers. The study recommends that senior managers engage themselves in word and in action in the implementation of RBM.